Design optimization of composite laminated structures using genetic algorithms and finite element analysis - Almeida, F.S.; Awruch, A.M. (Composite structures, 2009)
A technique for the design optimization of composite laminated structures is presented in this work. The optimization process is performed using a genetic algorithm (GA), associated with the finite element method (FEM) for the structural analysis. The GA is adapted with special operators and variables codification for the specific case of composite laminated structures optimization. Some numerical examples are presented to show the flexibility of this tool to solve different kinds of problems. Two cases of multiobjective optimization of plates under transverse or in-plane load are studied. In these examples the minimization of two objectives, such as weight and deflection or weight and cost, are simultaneously performed and a pareto-optimal set is obtained by shifting the optimization emphasis using a weighting factor. The stiffness maximization of a composite shell under pressure load is presented in the last example, where the geometrically nonlinear behavior of the structure is considered. Some aspects of the optimization performance, such as the apparent reliability and the computational cost, are investigated in each application.